Tripadivisor reviews: Users' multiple posts may be tampering with your online reviews research results - Perdigão, Filipa (2022)
Perdigão, F., Correia, M. B., & António, N. (2021). Tripadivisor reviews: Users' multiple posts may be tampering with your online reviews research results. In XIII International Tourism Congress, Reinventing tourism for upcoming challenges: Book of Abstracts (pp. 204-205). Centre for Tourism Research, Development and Innovation (CiTUR) . ------------------- Funding: The XIII International Tourism Congress, this Book of Abstracts and the articles authored by CiTUR Members were supported by national funds, through the FCT – Foundation for Science and Technology, under the project UIDB/04470/2020 CiTUR.